2023
DOI: 10.3390/insects14020152
|View full text |Cite
|
Sign up to set email alerts
|

Activity Patterns, Population Dynamics, and Spatial Distribution of the Stick Tea Thrips, Dendrothrips minowai, in Tea Plantations

Abstract: The stick tea thrips, D. minowai Priesner (Thysanoptera: Thripidae), is one of the most economically significant thrips pests of tea (Camellia sinensis (L.) O. Ktze.) in China. Here, we sampled D. minowai in tea plantations from 2019 to 2022 to characterize its activity patterns, population dynamics, and spatial distribution. A large proportion of D. minowai individuals were caught in traps placed at heights ranging from 5 cm below to 25 cm above the position of tender leaves at the top of the tea plant, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…However, current methods for controlling this thrips mainly rely on pesticide applications, which can seriously decrease tea quality and safety (Tewary et al, 2005;Ye et al, 2014;Nakai & Lacey, 2017). The aggregated distribution of D. minowai nymphs and females on tea leaves has been studied in detail (Zhang et al, 2019). Our analyses revealed a lack of aggregated D. minowai males in tea gardens, which differs from those of male aggregation observed for other thrips.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, current methods for controlling this thrips mainly rely on pesticide applications, which can seriously decrease tea quality and safety (Tewary et al, 2005;Ye et al, 2014;Nakai & Lacey, 2017). The aggregated distribution of D. minowai nymphs and females on tea leaves has been studied in detail (Zhang et al, 2019). Our analyses revealed a lack of aggregated D. minowai males in tea gardens, which differs from those of male aggregation observed for other thrips.…”
Section: Introductionmentioning
confidence: 60%
“…However, D. minowai nymphs and females form aggregations on tea leaves, but the males do not. A recent study indicated the D. minowai nymphs aggregate more than the females in tea plantations (Zhang et al, 2023). In addition, the aggregation pheromones may be secreted by both sexes and/or during the immature stages (eggs, nymphs/larvae, and pupae) (Wertheim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Both adults and larvae of D. minowai utilize their piercingsucking mouthparts to feed on the tender leaves of tea plants, leading to detrimental effects such as stunted growth, color fading, and even the development of leaf stiffness or brittleness. 5,6 Notably, there has been an increase in the incidence of D. minowai infestations, which results in higher tea plant damage annually and in turn significantly impacts tea yield and product quality. 5,7 Currently, control measures for D. minowai rely heavily on the application of chemical pesticides, including spinetoram, chlorfenapyr, and bifenthrin.…”
Section: Introductionmentioning
confidence: 99%
“…35 The aggregated distribution patterns of D. minowai larvae and adult females on tea leaves have been described in a previous study, the findings of which revealed that the larvae and adult females exhibit aggregation tendencies primarily along the veins of tender leaves. 6,36 Generally, adult females tend to assemble on the anterior surface of tea leaves, in clusters comprising ∼10-20 individuals. By contrast, larvae predominantly aggregate on the lower surface of leaves, forming groups of around 20-30 individuals.…”
Section: Introductionmentioning
confidence: 99%